Intercalibration of Mg Isotope Delta Scales and Realisation of SI Traceability for Mg Isotope Amount Ratios and Isotope Delta Values. Issue 3 (31st May 2020) - Vogl, Jochen; Rosner, Martin; Kasemann, Simone A.; Kraft, Rebecca; Meixner, Anette; Noordmann, Janine; Rabb, Savelas; Rienitz, Olaf; Schuessler, Jan A.; Tatzel, Michael; Vocke, Robert D.
Abstract : The continuous improvement of analytical procedures using multi‐collector technologies in ICP‐mass spectrometry has led to an increased demand for isotope standards with improved homogeneity and reduced measurement uncertainty. For magnesium, this has led to a variety of available standards with different quality levels ranging from artefact standards to isotope reference materials certified for absolute isotope ratios. This required an intercalibration of all standards and reference materials, which we present in this interlaboratory comparison study. The materials Cambridge1, DSM3, ERM‐AE143, ERM‐AE144, ERM‐AE145, IRMM‐009 and NIST SRM 980 were cross‐calibrated with expanded measurement uncertainties (95% confidence level) of less than 0.030‰ for the δ 25/24 Mg values and less than 0.037‰ for the δ 26/24 Mg values. Thus, comparability of all magnesium isotope delta (δ) measurements based on these standards and reference materials is established. Further, ERM‐AE143 anchors all magnesium δ‐scales to absolute isotope ratios and therefore establishes SI traceability, here traceability to the SI base unit mole. This applies especially to the DSM3 scale, which is proposed to be maintained. With ERM‐AE144 and ERM‐AE145, which are product and educt of a sublimation–condensation process, for the first time a set of isotope reference materials is available with a published value for the apparent triple isotope fractionation exponent θapp, the fractionation relationship ln α( 25/24 Mg)/ln α( 26/24 Mg). Abstract : Key Points: All artefact standards and reference materials for isotope amount ratios and delta values are calibrated against the primary isotope reference material ERM‐AE143. The DSM3 delta scale for Mg is thus anchored by ERM‐AE143 at −3.284‰ for δ 26/24 Mg with DSM3 representing δ 26/24 Mg = 0.000‰ ± 0.027‰.